2016
DOI: 10.1038/srep25318
|View full text |Cite
|
Sign up to set email alerts
|

Raffinose, a plant galactoside, inhibits Pseudomonas aeruginosa biofilm formation via binding to LecA and decreasing cellular cyclic diguanylate levels

Abstract: Biofilm formation on biotic or abiotic surfaces has unwanted consequences in medical, clinical, and industrial settings. Treatments with antibiotics or biocides are often ineffective in eradicating biofilms. Promising alternatives to conventional agents are biofilm-inhibiting compounds regulating biofilm development without toxicity to growth. Here, we screened a biofilm inhibitor, raffinose, derived from ginger. Raffinose, a galactotrisaccharide, showed efficient biofilm inhibition of Pseudomonas aeruginosa w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 40 publications
1
34
1
1
Order By: Relevance
“…in the human gut and has antiallergic properties in rats (21,35). Recently, raffinose was reported to inhibit the biofilm formation of Pseudomonas aeruginosa (36). In contrast, our study showed stimulatory effects of raffinose on biofilm formation by S. mutans in low concentrations of sucrose.…”
Section: Discussioncontrasting
confidence: 54%
“…in the human gut and has antiallergic properties in rats (21,35). Recently, raffinose was reported to inhibit the biofilm formation of Pseudomonas aeruginosa (36). In contrast, our study showed stimulatory effects of raffinose on biofilm formation by S. mutans in low concentrations of sucrose.…”
Section: Discussioncontrasting
confidence: 54%
“…The bacterial activities in the initial phase of biofilm formation can also affect important phenotypes, such as colony morphology, matrix formation and swarming motility (Kim et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Our data indicate that a potential therapeutic mechanism may be targeting biofilm formation, particularly in the initial process of bacterial attachment on the surface and proliferation, which involves the initial adhesion of bacterial surface proteins to the plastic surface. The bacterial activities in the initial phase of biofilm formation can also affect important phenotypes, such as colony morphology, matrix formation and swarming motility (Kim et al 2016…”
Section: Discussionmentioning
confidence: 99%
“…Despite years of study, it remains unclear whether galactinol, or any RFOs, are definitively required for, and directly involved in, seed vigor (Dierking and Bilyeu, 2009) or vegetative drought or cold tolerance (Amiard et al, 2003;Zuther et al, 2004). If required, the possible mechanisms of action (peripheral metabolic involvement [Kim et al, 2016], free radical scavenging [Nishizawa et al, 2008], sucrose crystallization inhibition [Leinen and Labuza, 2006]; water replacement [Martinez-Villaluenga et al, 2008], and the cellular component(s) affected [lipids, Hincha et al, 2003;proteins, Wendorf et al, 2004; general metabolic dampening, Sun and Leopold, 1997; or combinations of these]) remains obscure.…”
Section: Introductionmentioning
confidence: 99%